O conflito socioambiental no município de Silvânia/Goiás em razão da extração de areia no rio Piracanjuba: estudo de caso numa perspectiva jurídico-agrária - Faval, Rubia Mara Barbosa (2020)
This study, linked to the Postgraduate Program in Agrarian Law, Federal University of Goiás, research line: Agrifood Law, Territories and Development, consists of the analysis of socio-environmental conflict in the municipality of Silvânia, Goiás State, motivated by extraction. of sand on the Piracanjuba River, which runs approximately 120km in that municipality. Although this natural resource is a driver of economic development in the country, commonly used in the construction industry, its extraction results from an anthropic action that, if not well equated, can cause serious impacts on the environment, some of them irreversible, which are already perceived in the conflict analyzed here. The methodological procedure used was the documentary research, which analyzed public civil actions, conduct adjustment terms, public civil inquiries, inspection reports from environmental authorities, documents that demonstrate the resistance of the population in Silvânia, regarding the continuity of the sand extraction activity in the municipality and others, referring to the environmental licensing procedures with ANM and SECIMA, focused on the mining activity highlighted. For the development of the work the theoretical-descriptive method was used, through the analysis of the data obtained from the above mentioned material, combined with the interpretation based on the reading extracted from magazines, books, scientific articles, dissertations and theses related to the theme, besides the examination, constitutional and infraconstitutional legislative documents. The research has as theoretical reference the studies on environmental (in) justice, which gave a new connotation to the social and environmental conflicts, showing that there is not an equal distribution of the benefits and harms caused by the exploitation of the environment, which in fact was evidenced at the end of the analysis performed.